Detection and molecular characterization of a phytoplasma affecting Prunus persica L. in Jujuy, Argentina - Fernandez, Franco Daniel; Guzman, Fabiana; Curzel, Viviana; Bejarano, Noemí; Conci, Luis Rogelio (Springer, 2018)
Peach (Prunus persica L.) plants with symptoms of yellowing, reddening, curling and leaf necrosis, premature defoliation and internode shortening were observed in production fields in Jujuy province (Argentina). A phytoplasma was detected by PCR using the universal primer pairs P1/P7 and R16F2n/R16R2 in all the symptomatic samples analysed. The RFLP profile of PCR products, amplified with R16F2n/R16R2 primers, shows that this phytoplasma, named Argentinean Peach Yellows (ArPY), belongs to subgroup 16Sr III-B. The phylogenetic analysis of the 1244 bp 16S rDNA cloned sequence, grouped the ArPY phytoplasma into the X-disease group with a closer relationship with CFSD, PssWB and ChTDIII phytoplasmas. This is the first report of a phytoplasma infecting peach trees in Argentina.